Evaluation of the effects of the systemic proton pump inhibitor-omeprazole on periimplant bone regeneration and osseointegration: An experimental study - Gul, Mehmet; Dundar, Serkan; Bozoglan, Alihan; Ozcan, Erhan Cahit; Tekin, Samet; Yildirim, Tuba Talo; Bingul, Muhammet Bahattin (Elsevier B.V., 2022)
Objective: Investigations of the effects of proton pump inhibitors (PPIs) on bone healing have revealed that they affect bone regeneration negatively. The exact mechanism by which this adverse effect on bone tissue is not known. The aim of this study is to biomechanic and biochemical investigation of the effects of the PPIs on guided periimplant bone regeneration. Material & methods: Spraque dawley rats were divided controls (n = 8): there is no treatment during 8 week experimental period, PPI- Dosage 1 (n = 8) and Dosage 2 (n = 8): 5 mg/kg and 10 mg/kg omeprazol applied 3 times in a week with oral gavage during 8 weeks respectfully. Bone defects created half of the implant length circumferencial after implant insertion and defects filled with bone grafts. After experimental period the rats sacrified and implants with surrounding bone tissues were removed to reverse torque analysis (Newton), blood samples collected to biochemical analysis (glucose, AST, ALT, ALP, urea, creatinin, calcium, P). Results: Biomechanic reverse torque values did not revealed any statistical differences between the groups (P > 0,05). Conclusion: According the biomechanical and biochemical parameters PPIs does not effect the periimplant guided bone regeneration. © 2022 Craniofacial Research Foundation
Keywords: Guided bone regeneration; Omeprazole; Osseointegration; Proton pump inhibitors; Tibial bone